Introduction to Intersectionality (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. In this track, we'll explore the definitions of intersectionality, some concrete examples of intersectionality, why adopting an intersectional approach is so valuable, and the importance of intersectional allyship. Learning Objectives Explore the definitions of intersectionality Examine some concrete examples of intersectionality Learn more about why adopting an intersectional approach is so valuable, and Discover the the importance of intersectional allyship.